2012
DOI: 10.4103/0972-0707.97966
|View full text |Cite
|
Sign up to set email alerts
|

Root resection under the surgical field employed for extraction of impacted tooth and management of external resorption

Abstract: This case report illustrates determination of prognosis and immediate resection carried out, before completing the endodontic therapy, during the surgery employed for managing a nonperiodontal problem. This case showed external pressure resorption in the distobuccal root of maxillary second molar caused by the impingement of impacted third molar. Extraction of third molar was decided when healing was not seen, despite initiating endodontic therapy in second molar. Following elevation of flap and extraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“… 20 The aim of RCT is to stabilize the root resorption and to achieve a hermetic seal, but the poor prognosis due to severe bone loss around the resorbed root was evident. 21 If the resorption processes have progressed severely, both teeth may be not reservable. However, our previous cohort study revealed that, in most cases, this ERR tooth can keep vital pulp by just removing the ET without any other therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 20 The aim of RCT is to stabilize the root resorption and to achieve a hermetic seal, but the poor prognosis due to severe bone loss around the resorbed root was evident. 21 If the resorption processes have progressed severely, both teeth may be not reservable. However, our previous cohort study revealed that, in most cases, this ERR tooth can keep vital pulp by just removing the ET without any other therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Root resorption on the second molars is one of the complications associated with the third molar impaction and most of the available data have come from case reports [ 38 – 40 ]. Knutsson et al [ 41 ] evaluated 666 patients before removal of mandibular third molars and found that 548 patients had pathologic conditions (occlusal and/or distal caries, second molar root resorption and pericoronaritis).…”
Section: Discussionmentioning
confidence: 99%
“…For molars with periodontal, endodontic, restorative, or prosthetic problems, root resection therapy is a possible treatment option. Although the most common indications for root resection are periodontal-based, our discussion focuses on endodontic indications, such as an unfillable canal, root fracture, root perforation, root resorption, and root decay [ 22 ]. Root resection therapy can provide good outcomes in cases of incomplete fracture [ 23 ].…”
Section: Root Amputation Root Resection or Hemisectionmentioning
confidence: 99%